Tariffs, Technology Transfer, and Welfare - Feenstra, Robert C.; Judd, Kenneth L. (Journal of Political Economy, 1982)
It is found that the welfare gain per unit of revenue raised is maximized for an export tariff on technology transfer, followed by an import tariff on goods, with an export tariff on goods the poorest policy alternative. These results are derived within a monopolistic competition model, where the production of any good requires some initial research and development (R&D), and technology transfer occurs when R&D is done in one country for production of goods in the other. An intuitive explanation is presented, based on the public-good nature of R&D and also the elasticity of demand for technologies from firms.